Non-Progression among Higher Education New Entrants: a Multivariate Analysis - MC COY, SELINA (Higher Education Authority, 2010)
Internationally attention is increasingly focused on how students fare after entry to college?on student experiences in relation to retention, completion and withdrawal.48 However while research is increasingly focused on student experience and performance within higher education, the vast majority of studies are based on single-institution data.49 To assess the extent to which institutions vary in their non-progression rates, it is important to take account of the composition of the student body, in terms of prior educational attainment in the Leaving Certificate examination or socio-economic profile, to allow a more like-for-like comparison of institutions.
A Study of Progression in Irish Higher Education
PUBLISHED
Dublin
Keywords: Education; Irish third-level